Shared clinical and immunologic features of mRNA vaccines: preliminary results from a comparative clinical study - Carlos Fierro; Nelia Sanchez-Crespo; Daniel Makrinos; Weijie Zhang; Yanbo Sun; Poonam Rohilla; Bethany Girard; Abidemi Adeniji; Anthony DiPiazza; Robert Paris (Frontiers in Immunology)
IntroductionClinical trials do not typically assess underlying molecular mechanisms of vaccine immunogenicity or reactogenicity. We evaluated the reactogenicity and immunogenicity of 4 mRNA vaccines and potential contributing mechanisms and identified shared and unique clinical and immunologic features.MethodsThis ongoing, open-label, phase 1 trial randomized healthy adults (18-75 years) to receive a single dose of mRNA-1273.222 (bivalent COVID-19), mRNA-1345 (RSV), mRNA-1010 (influenza), and FLUAD (active influenza comparator) or 2 or 3 doses of mRNA-1647 (CMV). The primary objective was to assess the safety and reactogenicity of each study vaccine, with humoral immunogenicity (neutralizing antibody [nAb] responses) as the secondary objective. This interim analysis reports safety and reactogenicity in all study vaccines and humoral immunogenicity in single-dose vaccines (mRNA-1273.222, mRNA-1345, mRNA-1010, and FLUAD). Exploratory objectives included antigen-specific T-cell responses after single-dose mRNA-1345 or mRNA-1273.222, and soluble mediators of inflammation and innate immunity following vaccination in single-dose vaccine groups and two doses of mRNA-1647.ResultsAt the interim analysis data cutoff (February 1, 2023), 302 participants received 1 dose of the study vaccines. Reactogenicity exhibited a consistent trend across vaccine groups; most solicited local and systemic adverse reactions within 7 days were mild or moderate in severity. There were no deaths or serious, severe, or treatment-related adverse events leading to study discontinuation. At Day 29, nAb titers against vaccine-specific antigens increased 2- to 8-fold versus baseline for all single-dose vaccine groups. In an exploratory analysis, mRNA-1273.222 and mRNA-1345 induced antigen-specific Th1-biased CD4+ and CD8+ T-cell responses at Day 29. The cytokine response analysis showed increased levels of IFN-γ, IL-6, IL-2Ra, CXCL9, IP-10, MCP-2, and MIP-1β on Day 2 following vaccination, with generally greater increases observed with mRNA vaccines versus FLUAD. Regardless of age and across mRNA vaccine groups, peak serum levels of IL-1Ra and MCP-1/MCP-2 on Day 2 weakly correlated with systemic reactogenicity scores (correlation coefficient range: 0.15-0.27).ConclusionsThe 4 mRNA vaccines had acceptable reactogenicity, demonstrated changes in serum biomarkers of innate immune activation, and were immunogenic. This suggests that the observed reactogenicity of mRNA vaccines may be related to shared features of the mRNA platform (LNP platform).Clinical trial registrationClinicalTrials.gov, identifier NCT05397223.